Peluang Kerja Perempuan Lulusan Sekolah Menengah Kejuruan Perhotelan di Bali - Ni Made Ary Widiastini; Made Aristia Prayudi; Gede Wirata; Nyoman Dini Andiani; Ni Luh Putu Agustini Karta (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This study aims to find out how job opportunities for female graduates of vocational schools to be accepted as employees in hotels. Research data were collected through questionnaires using Google forms using probability sampling techniques and interviews with the Tremblay method for selected Human Resources (HR) Departments. Sample analysis shows that 45% of SMK graduates are accepted as day laborers; 28.30% are contract employees; 18.30% are permanent employees. Especially for Vocational female graduates 27.22% have an opportunities to work in housekeeping, 21.30% in the front office, 21.30% in food and beverage production, 24.86% in food and beverage service and other departments both as technicians and administration as much as 5.40%. Specifically for the admin position, graduates must have hotel operations administration skills, but vocational graduates are still lacking in mastering the system. This article argues that hotels open themselves to accept vocational school graduates including women, and to be able to become permanent employees, graduates must have adequate skills. Keywords: job opportunity, women graduate, hotel vocational school, Bali.